Persevering Despite Physical and Mental Exhausting: A Novice nurse's Experience as a Volunteer Nurse Caring for Patients in the Covid-19 ICU Room - Vebby Astri Rizkilia; Asti Melani Astari; Dina Dewi Sartika Lestari Ismail (Universitas Aisyah Pringsewu, 2023)
Most volunteer nurses in the covid-19 ICU are novice nurses. They have no experience working in the ICU or ICU training. They met the limitations of receiving training. The workload and challenges in the covid-19 ICU room are heavier than in the common ICU. This study aimed to explore the experience of novice nurses as volunteer nurses caring for patients in the covid-19 ICU room. This study used a qualitative method with an interpretive phenomenological approach. Ten participants are covid-19 ICU volunteer nurses from the two largest covid-19 referral hospitals in Malang and Batu City who were selected using the purposive sampling method. Data collected used In-depth interviews. Data analysis used the Interpretative Phenomenological Analysis method. There are eight themes found: (1) Feeling insecure working in the covid-19 ICU room; (2) Facing rapid adaptation when initially assigned; (3) I need ICU training; (4) Persevering faced all conditions in the Covid-19 ICU room; (5) Frustrated and Distraught Facing Patients; (6) Trying to be strong in dealing with the patient's family; (7) Grateful to have the opportunity to become a covid-19 ICU volunteer nurse; and (8) Expecting career and life improvements in the future after completing a period of duty as a covid-19 ICU volunteer nurse. ICU covid-19 volunteer nurses experience physical and mental exhausting while caring for patients. Peer support is one of the factors that can make them persevere. They need other physical and mental support while caring for patients in the covid-19 ICU room